PENGETAHUAN REMAJA UMUR 16-18 TAHUN TENTANG NAPZA DI KELAS 2 SMA YAYASANÂ Â PENDIDIKAN DAERAH TRAWAS KABUPATEN MOJOKERTO - Zainuri, Imam; Sunariyo, (JURNAL KEPERAWATAN BINA SEHAT, 2012)
NAPZA(Narcotic Drugs, Psychotropic Substances, an addictivesubstance) is amaterialorsubstance thatmayaffect thepsychiatric/psychologicalperson (thoughts, feelings, behavior) and canlead todependencefsikandpsychology. From the results ofa preliminarystudyof dataobtained byhigh school studentsTrawasRegionalEducation FoundationMojokertoregencyobtained6 of10 students(60%) did not knowaboutdrug abuse. The purposeof this studyto determine theknowledge ofadolescentsabout thedrugatthe RegionalHigh SchoolEducation FoundationTrawasMojokertoregency.The study designused isdescriptive. The study populationwasallstudents in grade2 SMAMojokertoEducation Foundationa total of 32respondents. SamplingcollectiontechniqueusedTotalsampling. Collectingdata usingquestionnaires.Results showedthat 20respondents(58.33%) knowledgeableenough about thedrugatthe RegionalHigh SchoolEducation FoundationTrawasMojokertoregency.Knowledge of respondents about NAPZA is simply caused by lackof curiosity sothatstudentsfromthe school to involve students inplanning, prevention and control ofNAPZA in schools.Keywords: Knowledge, Youth,NAPZA